Rotating Machinery, Hybrid Test Methods, Vibro-Acoustics & Laser Vibrometry, Volume 8 Proceedings of the 34th IMAC, A Conference and Exposition on Structural Dynamics 2016 - De Clerck, James; Epp, David S. (Conference Proceedings of the Society for Experimental Mechanics Series,, 2016)
Rotating Machinery, Hybrid Test Methods, Vibro-Acoustics & Laser Vibrometry, Volume 8.Proceedings of the 34th IMAC, A Conference and Exposition on Dynamics of Multiphysical Systems: From Active Materials to Vibroacoustics, 2016, the eighth volume of ten from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: • Processing Modal Data • Rotating Machinery • Vibro Acoustics • Laser Vibrometry • Teaching Practices • Hybrid Testing • Reduced Order Modeling.